TrashGo: Sistem Informasi Manajemen Barang Rongsok Berbasis Perangkat Bergerak Menggunakan Metode Spiral - Nani Irma Susanti; Yusuf Sutanto; Adnan Tery Suseno (Jurnal Bengawan Solo Pusat Kajian Penelitian dan Pengembangan Daerah Kota Surakarta, 2026)
Traditionally, individuals wishing to sell scrap or secondhand goods often rely on waiting for mobile collectors to pass by, which is inefficient and time-consuming. Furthermore, the prices of certain scrap items frequently fluctuate without the seller's knowledge, leading to a lack of transparency and fairness in transactions. To address these issues, this study developed a smartphone-accessible system designed to streamline and facilitate transactions for secondhand goods. This research introduces Trashgo, a Spiral-model-based application that serves as an online platform for trading waste and scrap materials. The system features a dynamic pricing mechanism that updates in real-time, keeping users informed of current market values and enabling them to make informed decisions. Additionally, the application integrates Location-Based Services (LBS), allowing for real-time tracking of both collectors and customers, optimizing logistics and simplifying the pick-up process for scrap dealers. By facilitating faster and more efficient transactions, Trashgo aims to enhance the overall user experience, ensuring that both buyers and sellers benefit from fair pricing and improved convenience. The implementation of Trashgo seeks to foster efficient and transparent transactions, ultimately contributing to the reduction of waste and the promotion of sustainable practices within the secondhand goods market.